EFFECTS OF SHOES ON KINETICS AND KINEMATICS OF THE SQUASH FORWARD LUNGE IN MALE PLAYERS - Sinclair, Jonathan; Bottoms, Lindsay; Taylor, Paul John; Mahmood, Khizar (Kinesiology, 2017)
Squash is associated with a high incidence of chronic injuries. Currently there is a trend in many sports for players to select minimalist footwear. The aim of the current investigation was to examine the effects of squashspecific, running shoes and minimalist footwear on the kinetics and 3-D kinematics of the lunge movement in squash players. Twelve male squash players performed lunge movements whilst wearing minimalist, running shoe and squash-specific footwear. 3-D kinematics of the lower extremities were measured using an eightcamera motion analysis system alongside kinetic and tibial acceleration information which were obtained using a force platform and an accelerometer. Differences between footwear were examined using one-way repeated measures ANOVA. The results show firstly that loading rate parameters were significantly greater in the minimalist (average = 85.36B.W/s and instantaneous = 179.09B.W/s) footwear in relation to the squashspecific (average = 38.66 B.W/s and instantaneous = 50.73B.W/s) and running footwear (average = 37.62B.W/s and instantaneous = 48.14B.W/s). In addition, tibial acceleration parameters were also significantly greater in the minimalist (peak tibial acceleration = 8.45 g and tibial acceleration slope = 422.28g/s) footwear in relation to the squash-specific (peak tibial acceleration = 4.33 g and tibial acceleration slope = 182.57g/s) and running footwear (peak tibial acceleration = 4.81 g and tibial acceleration slope = 226.72g/s). The significant increase in impact loading in the minimalist footwear therefore suggests this type of shoe may place squash players at an increased risk of developing impact-related chronic injuries. Key words: biomechanics, footwear, squash